RETRACTED ARTICLE: Emodin enhances osteogenesis and inhibits adipogenesis - Feng Yang; Pu-wei Yuan; Yang-Quan Hao; Zheng-Mao Lu (BMC Complementary and Alternative Medicine)
Abstract Background It has been suggested that the formation of osteoblasts in bone marrow is closely associated with adipogenesis, and the balance between osteogenesis and adipogenesis differentiation of MSCs (mesenchymal stem cells) is disrupted in osteoporosis. In order to improve the treatment of osteoporosis, available agents with roles of regulating the balance is highly desirable. Emodin is a natural anthraquinone derivative extracted from Chinese herbs, which have been used to treat bone diseases for thousands of years. However, the underlying molecular mechanisms of emodin in modulating osteogenesis and adipogenesis remain poorly understood. Methods The molecular mechanisms of emodin on the processes of osteogenesis and adipogenesis in ovariectomized mouse and BMSCs (bone marrow mesenchymal stem cells) have been studied. We have analyzed the effects of emodin in vivo and in vitro. Female ICR mice were assigned to three groups: sham group, ovariectomy group, emodin group. Efficacy was evaluated by H&E, immunohistochemical assay and Micro-CT. In vitro, we analyze the effect of emodin—at concentrations between 0.1 μM and 10 μM-on the processes of inducing osteogenesis and inhibiting adipogenesis in BMSCs by ALP, Oil red O staining, real time RT-PCR and western blot. Results As our experiment shows that emodin could increase the number of osteoblast, BMD (bone mineral density), BV/TV (trabecular bone volume fraction), Tb.N (trabecular number) and Conn.D (connectivity density) of OVX (ovariectomized) mice and decrease the bone marrow fat tissue and adipocytes. The genes and proteins expression of osteogenesis markers, such as Runx2, osterix, collagen type I, osteocalcin, or ALP were up-regulated. While, the genes and proteins involved in adipogenesis, PPARγ, C/EBPα and ap2 were down-regulated. Conclusion It proves that emodin inhibits adipocyte differentiation and enhances osteoblast differentiation from BMSCs.